2019
DOI: 10.1371/journal.pone.0212279
|View full text |Cite
|
Sign up to set email alerts
|

A multifactorial approach of nutritional, intellectual, brain development, cardiovascular risk, socio-economic, demographic and educational variables affecting the scholastic achievement in Chilean students: An eight- year follow-up study

Abstract: The aim of this study was to quantitate the relative impact of nutritional, intellectual, brain development, cardiovascular risk, socio-economic, demographic and educational variables on the results of the 2009 Quality Education Measurement System (SIMCE) tests of language and mathematics for scholastic achievement (SA) applying a multifactorial approach, in school-age children of the 2010 5 th elementary school grade (5ESG) and of the 1 st grade of high school (1H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…Given the low level of FVs consumption among in-school adolescents in Ghana, the academic achievement of these adolescents may be hindered since cognitive and intellectual development requires adequate food nutrients for the brain to function efficiently and effectively [46,47]. Therefore, adequate nutrition should be provided for in-school adolescents in Ghana as this will help in achieving academic excellence.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low level of FVs consumption among in-school adolescents in Ghana, the academic achievement of these adolescents may be hindered since cognitive and intellectual development requires adequate food nutrients for the brain to function efficiently and effectively [46,47]. Therefore, adequate nutrition should be provided for in-school adolescents in Ghana as this will help in achieving academic excellence.…”
Section: Discussionmentioning
confidence: 99%
“…First, the cross-sectional design could not address the causal effects of academic stress variables on overweight and obesity among college students. Other factors associated with academic stress (e.g., the intellectual ability and head circumference) [35] and the nutritional status (e.g., dietary intake, physical activity) [36] of college students need to be investigated and considered in future work. It is important to continually monitor changes in academic stress over time alongside changes in nutritional status to observe possible effects of each other in cross-lagged analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The learning process is a multidimensional issue that depends on several elements related to the child, the families, and the educational system 1 3 . Studies about scholastic achievement (SA) have shown that several neurobiological factors impact academic performance.…”
Section: Introductionmentioning
confidence: 99%